ANALISIS PENGARUH KABEL TANAH TERHADAP TRANSFER VOLTAGEDENGAN VARIASI LUAS PENAMPANG KABEL DAN JARAK GARDU - Budi Santoso; Muchamad Nur Qosim; Husnul Khatimah Azhari (Sekolah Tinggi Teknik - PLN, 2016)
Connection between substations and distribution substations using ground cables often occurs due to mechanical, thermal, and over voltage faults or due to defective or damaged materials. The disturbance flow will flow on metal parts of the equipment and also flow in the ground around the substation. The purpose and benefits of this study was to analyze the differences in the impedance value of the cable sheath at the distribution substation to the value of the voltage change (transfer voltage) dipengaruh by land lines, using data cable PT Sucaco Tbk, cable type of three core types NA2XSEBY with cross-section 70 mm2, 150 mm2, 240 mm2 and two substations are a substation a and substations b with different distances of 400m, 500m, 600m, 700m, and 800m, assumed soil resistivity is 100Ωm, with 1m cable burial depth. The greater the distance between the substation then the ratio of voltage increase at the source with the transfer voltage will be smaller, which for the cross-sectional area of the cable 70 mm2 with a distance of 400 m then kt 0.9098, while for a distance of 500 m of 0.88862, for 600 m of 0.8717 , For 700 m of 0.8112, and for 800 m to 0.7422. The bigger cross section of the ground cable, the greater the kt ratio, it is seen in the substation with a distance of 500m where the area of cross-sectional 70 mm2 then the big kt is 0.8862, while for 150 mm2 of 0.9207, and for 240 mm2to 0.9212.